Piezo‐Phototronic Effect on Performance Enhancement of Anisotype and Isotype Heterojunction Photodiodes. (24th May 2018) - Pan, Zijian; Peng, Wenbo; Li, Fangpei; He, Yongning
Abstract: The piezo‐phototronic effect is confirmed as a promising methodology to optimize the performance of optoelectronic devices. However, not only positive effects, but also negative effects may be produced in some types of photodiodes (PDs) by the piezo‐phototronic effect, resulting in the restriction of the PDs' photoresponse performance enhancement. In order to obtain the largest possible photoresponse performance enhancement, it is essential to investigate how the piezo‐phototronic effect influences the photoresponse performance of PDs with different device configurations and structures. Here, the piezo‐phototronic effect on the photoresponse performance enhancement of anisotype (p‐Si/n‐ZnO) and isotype (n‐Si/n‐ZnO) heterojunction PDs is thoroughly investigated. The experimental results show that the piezo‐phototronic effect induced improvement of the p‐Si/n‐ZnO heterojunction PD is much larger than that of the n‐Si/n‐ZnO heterojunction PD. The energy band diagrams under compressive strains are carefully analyzed, revealing that two positive effects are introduced to the p‐Si/n‐ZnO heterojunction PD, whereas one positive and two negative effects are introduced to the n‐Si/n‐ZnO heterojunction PD by the piezo‐phototronic effect. This work presents an in‐depth understanding about the piezo‐phototronic effect on the photoresponse performances of PDs with different device configurations and structures. Abstract : Anisotype and isotype heterojunction photodiodes are demonstrated, and piezo‐phototronic effects are introduced to enhance the photoresponse of both kinds of photodiodes to 405 nm laser illumination. Different magnitudes of the performance improvements by the piezo‐phototronic effect are obtained for the anisotype and isotype heterojunction photodiodes, which is found to originate from their different device configurations and structures.